2003
DOI: 10.1074/jbc.m305697200
|View full text |Cite
|
Sign up to set email alerts
|

A Predominant Role for Inhibition of the Adenylate Cyclase/Protein Kinase A Pathway in ERK Activation by Cannabinoid Receptor 1 in N1E-115 Neuroblastoma Cells

Abstract: Cannabinoids activate several members of the mitogen-activated protein kinase superfamily including p44 and p42 extracellular signal-regulated kinase (ERK). We used N1E-115 neuroblastoma cells and the cannabinoid receptor agonist WIN 55,212-2 (WIN) to examine the signal transduction pathways leading to the activation of ERK. ERK phosphorylation (activation) was measured by Western blot. The EC 50 for stimulation of ERK phosphorylation was 10 nM, and this effect was blocked by pertussis toxin and the CB1 (canna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 42 publications
2
53
0
4
Order By: Relevance
“…Activation of CB1 receptors stimulates a pertussis toxinsensitive G protein and inhibits adenylyl cyclase and PKA, leading to a decrease in constitutive phosphorylation of c-Raf at the inhibitory site (Ser259) and an increase in ERK phosphorylation (Davis et al 2003). ERK is known to be required for several forms of synaptic plasticity and learning and memory (English and Sweatt 1997;Impey et al 1998;Atkins et al 1998;Coogan et al 1999;Schafe and LeDoux 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of CB1 receptors stimulates a pertussis toxinsensitive G protein and inhibits adenylyl cyclase and PKA, leading to a decrease in constitutive phosphorylation of c-Raf at the inhibitory site (Ser259) and an increase in ERK phosphorylation (Davis et al 2003). ERK is known to be required for several forms of synaptic plasticity and learning and memory (English and Sweatt 1997;Impey et al 1998;Atkins et al 1998;Coogan et al 1999;Schafe and LeDoux 2000).…”
Section: Discussionmentioning
confidence: 99%
“…8A). Recent data have suggested that CB 1 R-induced activation of p42/44 MAPK (ERK1/2), which was formerly suggested to occur via G-protein-dependent pathways (Galve-Roperh et al 2002, Davis et al 2003, Dalton & Howlett 2012, is also mediated by b-arrs (Ahn et al 2013a, Mahavadi et al 2014. Therefore, we aimed to study how the ERK1/2 responses correlate with the G-protein activation and/or b-arr recruitment of the biased CB 1 R mutants.…”
Section: B-arr1 Recruitment Of Cb 1 R-aay Mutant Is Robustly Enhancedmentioning
confidence: 99%
“…The CB 1 receptor, via canonical Gi-mediated inhibition of adenylyl cyclase, decreases cAMP concentration, and this in turn plays a prominent role by de-inhibiting the ERK pathway by protein kinase A [49,50]. In addition, G protein bg subunits liberated upon CB 1 receptor activation stimulate the ERK pathway in a PI3K-dependent manner [51].…”
Section: Cannabinoid Signalling In Neuralmentioning
confidence: 99%